Assessing the Challenges and Negative Influences of the Internet on Young People in Pakistan - Dr. Aisha Bibi; Dr. Khan Faqir; Saima Rahman; Uzma Rahman (Social Science Review Archives, 2025)
This paper will explore and assess the misuse of the internet and its negative impacts upon the young generation in Pakistan. Internet has detrimental effects on their mental health, academic performance, social development, cultural and societal values. Young people in Pakistan are increasingly using the internet, which has resulted in a rise in problematic online behaviors that negatively impact their mental, academic, social, and physical health. Though its educational, communication, and entertainment benefits are innumerable, its unchecked use has had several detrimental effects. The psychological strain brought on by continuous exposure to idealized images on social media is also examined, as it contributes to problems with body image and low self-esteem. Excessive internet use has been shown to be strongly linked to increased anxiety, depression, sleep disturbances, and a decline in emotional maturity. The unchecked use of the internet is harmful to the younger generation in all over the world and especially in Pakistan. It delves into the psychological, social, academic, and cultural consequences of internet use, including mental health issues, decreased academic performance, social isolation, and the erosion of traditional and cultural values. The study underscores the importance of responsible internet use and advocates for a collaborative effort involving parents, educators, and policymakers to protect youth from its potential harm. Nowadays all the evils in a society specially in Pakistani society spread due to the negative use of internet which badly impact the mental level of young generation, and they mislead them mentally, socially, educationally, religiously, culturally and traditionally. Overuse, however, has resulted in several detrimental effects on attention span, academic performance, and personal growth. Such type of negative impacts of internet is a poison killer for youngster in overall the world and especially in Pakistan.